Keefektifan Google Classroom sebagai media pembelajaran - Sabran Sabran; Edy Sabara (Seminar Nasional LP2M UNM, 2019)
The research objectives were: (1) to determine the effect of the application of Google Classroom on the teaching and learning process in the classroom and outside the classroom, (2) to identify the effectiveness of designing and making learning materials at Google Classroom, (3) to identify the effectiveness of learning implementation with Google Classroom, and ( 4) knowing the response of students to learning using Google Classroom applied to the teaching and learning process. This study is an evaluation study with a discrepancy model. The evaluation of the discrepancy model is a program gap evaluation, seeing the program gap that occurs between what is expected and the implementation of the program (reality). The standard of implementation used in google classroom learning evaluation in this study is the quality standard for implementing e-learning that has been developed by several universities. The study was conducted in the department of electronic engineering education in multimedia learning subjects. Samples were taken by purposive sampling method, that is, from the mahapean population and students who attended the lecture. The achievement of the effectiveness of the implementation of google classroom learning from each variable is the learning planning component, the component of designing and making the material, the component of learning delivery, and the evaluation component of the implementation are all quite effective.